Soil management and territorial development tools (2019)
The evaluation of the tax performance of the Municipalities and the development obtained, by these, allows us to establish that some of them have achieved a more dynamic process, which is mainly related to the authorization of soils for different economic activities and the application of some tools such as surplus value, development through partial plans, the affectation of land for public works, the cadastral update among others, which in addition to influencing the construction of the city, allow an important financial management, which energizes the territory, however These decisions are sometimes not taken as a result of the integral evaluation of the territory and its capacity to sustainably support the proposed uses, which causes a problem that deteriorates the quality of life of the human being that lives that territory Therefore, it is necessary that the execution of the land occupation policies be done under the objective of achieving real development and with the concept of integrality; it cannot be pretended that only some territories enjoy resources, and less economic dependence, because of the location of more productive activities on their land, while others must bear the negative consequences of those decisions taken in isolation and without understanding that development It cannot be limited to one sector, since the territory in spite of its administrative political division is only one, and requires an integral view of it.